William James Chalmers papers - Chalmers, William James, 1852-1938.
Correspondence, clippings, and printed matter. Includes letters from Roger A. Burrell, soldier at the European front; exchanges with Walter McDermott, British mining engineer and metallurgist; James Hamilton Lewis; Francis Stuyvesant Peabody, chairman of the Committee on Coal Production of the Council of National Defense; and R.T. Bayliss, London manufacturer. Subjects include English and American politics and the progress of the war.
Executive of the Allis Chalmers Company and civic leader.
Collection material in English.
Keywords: Bayliss, R. T. -- Correspondence; Burrell, Roger A. -- Correspondence; Lewis, James, -- 1863-1939 -- Correspondence; McDermott, Walter -- Correspondence; Peabody, Francis Stuyvesant, -- 1859-1922; United States. -- Council of National Defense; Mines and mineral resources -- Great Britain; World War, 1914-1918 -- France; World War, 1914-1918 -- Germany; Businessmen; Civic leaders